Arquitetura e urbanismo : estratégias profissionais, disputas mercadológicas e ascensão profissional - Pacheco, Cristiano Ricardo de Azevedo (2018)
This dissertation aims to analyze the architects and their spaces of professional activity, in particular, analyze the social, institutional and political circumstances of professional participation in labor market instances. The departure of the architects of the previous Federal Council of Engineering, Architecture and Agronomy (CONFEA) and the creation of the new Council of Architects and Urbanists (CAU) brought to the fore debates about the extra-professional confrontations and the possible strategies of market reserve. In this sense, the discussions about the installation of the new representative council of the architects made it possible to show the struggle for the definition of investments for professional insertion and career ascension. In this way, the agents use a set of accumulated resources related to the social origins and the insertion in diverse social spheres. However, the extra-professional confrontations for imposition of performance and attributions of distinct professions were not only revealing a struggle for space in the labor market, but also made it possible to show an internal division, among the architects, stimulated by diversification of opinions related to the forms and behavior in the labor market. In order to understand the conflicts in analysis, it was fundamental to assimilate the system of social relations that architects establish among themselves, among other actors and with the labor market. For this, it was necessary to research the corporate and informal actions, to apprehend the social dynamics and the professional culture of the group of architects and urban planner. Thus, the spaces of action were analyzed, revealing the professional relations from the entry of new actors in a market considered restricted by the architects and urban planner. On one hand, the empirical universe is composed by the architects established in Aracaju, which are considered protagonists in the local market, and on the other, by the Council of Architecture and Urbanism of Sergipe. During the work, we studied their biographical and professional trajectories. To fulfill the purposes presented here, we subdivided this research into three main stages. In the first moment, we made a historical study of the process of structuring the field of action of the architect, distinguishing the actors that compose this space and how the discussions of professional socialization happened. In the second moment, we investigated what the architect does in practice and what his main spaces of action, discerning the social, political and economic influences that reflected in the trajectory of the profession. Finally, we identified the contents and forms of sociability of the protagonist architects who invest in the main fields of professional activity, based on changes in the labor market after the new professional regulation. This dissertation made it possible to demonstrate how the spaces of action of the architects show the formulations about the labor market and its position as architect and urbanist in front of the other actors, among their peers and before society. The present research allowed to testify that the exercise of architecture and urbanism activity is associated to the competence of application in several areas and that this proactive condition is determinant for the success in the professional trajectory. The present research corroborated that the exercise of the architecture and urbanism activity is associated to the competence of application in several areas and that this proactive condition is determinant for the success in the professional trajectory. In addition, here, there is information that allowed the understanding of the collective history of the profession and, in this way, made possible to recognize the resources that describe the investments in the profession of architecture and urbanism.